An efficient methodology for robust assignment problem. (2018) - Zaman, Kais; Saha, Subrata Kumar
This paper proposes formulations and algorithms for assignment problem under natural or physical variability, from the perspective of robustness of the assignment. We formulate the robust assignment problem as a nonlinear binary programming problem. An equivalent linear binary programming formulation and a modified Hungarian approach are then proposed to achieve computational efficiency. The proposed methods are illustrated for two example problems, where the information on the problem parameters is available as their means and standard deviations.